The early development of the Patagonian squid Loligo gahi D’Orbigny, 1835 in Peruvian Waters (Cephalopoda: Loliginidae) - Cardoso, Franz (2005)
The early development of the Patagonian squid, Loligo gahi D’Orbigny,1835, was studied in the field and in the laboratory. Egg strands, spawned off San Lorenzo Island, Peru, were collected, carried to the laboratory, and incubated in a closed sea water system. Egg capsules ranged from 88 to169 mm in length, and each capsule contained between 56 and 114 fertilized eggs. Individual eggs ranged from 1,7 to 2,1 mm in length, and the mantle length of hatchlings varied from 1,9 to 2,8 mm. Development took about 20 days at a mean temperature of 19 ºC. The pattern of embryonic development is similar to that previously observed in other species of Loligo. Following hatching, paralarvaes survived for 45 days with a diet of zooplankton (copepods, mysids and polychaete larvaes).